Effects of auxiliary magnetic field strength and direction on material removal rate and surface roughness in magnetic field-assisted electrical discharge machining. (April 2023) - Zabihi, Seyed Sina; Etemadi Haghighi, Shahram; Soleimanimehr, Hamid; Maghsoudpour, Adel
Abstract: Magnetic field-assisted electrical discharge machining (MFEDM) has recently been used to optimize and improve output parameters in electrical discharge machining (EDM). Research on the MFEDM method shows that the use of an auxiliary magnetic field in EDM can significantly improve the MRR, TWR, surface roughness and surface integrity. In this research, the effect of the strength and direction of the auxiliary magnetic field in MFEDM was investigated, which has not yet been focused on. Two groups of experiments were performed on the CK45 steel alloy. MRR and surface roughness were considered as output parameters. It was found that maximizing MRR requires an optimal magnetic field strength, such that a deviation from the optimal field strength reduces the MRR. In addition, the direction of the auxiliary magnetic field was effective on MRR and surface roughness, so that the highest MRR was obtained when the direction of the auxiliary magnetic field was parallel to the plasma channel, and the lowest surface roughness was obtained when the direction of the magnetic field was chosen against the plasma channel.